Investigating the relationship between process use and use of evaluation findings in a government context - Amo, Courtney (University of Ottawa (Canada), 2009)
Despite support for the notion that evaluation utilization is facilitated by stakeholder engagement, evaluation practice in the Government of Canada may not be conducive to such engagement. This mixed-methods study explores the extent to which process use is manifest within government; the conditions, influences and factors that enhance process use; and the relationship between process use and findings use. The study supports the notion that process use and its consequences are important predictors of findings use in government. The level of stakeholder engagement present in this context appears to support the development of knowledge/skills, which may not be sufficient in enhancing findings use; changes in attitude/affect and in actions/behaviours may be of greater importance. This study highlights the importance of timely, higher-level engagement over frequent, surface-level engagement, as well as the importance of organizational learning capacity and conditions mediating evaluation use in setting the stage for process use to occur.
Keywords: Education, Tests and Measurements.; Political Science, General.